Consulting support of the project management development in conditions of society informatization - Chukhrai, N. I.; Novakivsky, I. I. (Publishing House of Lviv Polytechnic National University, 2015)
The article justifies the necessity of changing the management paradigm in the emerging information society. It is proved that project management is a determinant factor in cooperation of businesses during globalization. The processes of consulting environment formation as the basis of information support and the expansion of the project management application scope are analyzed. There are proposed measures to improve the project management methodology and to promote its dissemination.
Keywords: project management; businesses; ecosystem; information infrastructure; information society; information